Penerapan Metode STIFIn dalam Menghafal Al-Qur'an di Pondok Pesantren Al-Fuad Fahmi - Kholidatun Nur Wahidiyah; Nasrulloh Nasrulloh; Muhammad Fadlan (Jurnal Studi Al-Qur'an, 2025)
Quran memorization methods are a field that continues to experience significant development. Recently, a method originating from psychology, the STIFIn method introduced by Dr. Farid Poniman, has improved Quran memorization techniques. This article aims to analyze the implementation of the STIFIn method at the Al-Fuad Fahmi Islamic Boarding School located in Palasari Village, Tangerang. This study uses a qualitative approach through field research methods, where data is obtained through interviews and observations. The results show that there are five types of intelligence—Sensing, Thinking, Intuiting, Feeling, and Instinct—which are used to identify the potential of each student through fingerprint testing. The results of this test are stable and do not change even though it is administered repeatedly. Implementing the STIFIn method at the Al-Fuad Fahmi Islamic Boarding School is going well. However, several challenges must be overcome to achieve optimal results according to the boarding school's expectations. The recommendation from this study is to improve training and support for teachers in implementing the STIFIn method, as well as to overcome existing obstacles so that students can optimize their potential in memorizing the Qur'an.